CHALLENGES AND ISSUES FOR (THE RIGHT TO) AFFORDABLE HOUSING IN CROATIA (EU and comparative law issues and challenges series (ECLIC), 2024)
Real estate prices in the 2020s reached record figures for purchases in the Republic of Croatia, Europe and beyond, and with the increase in real estate prices on the market, apartment rents also rose. The cost of living is extremely high, loans are more and more expensive and unattainable, interest rates are high, recession and inflation dominate, all of which affects real estate prices that are too high for an increasing number of citizens. The focus of the work is not the most vulnerable groups of the population who already live below the poverty line and are fully exposed to state and social assistance, but mid-income groups who are often unjustifiably ignored on the scale of those whose rights to housing are threatened. The paper contributes to the understanding of the problem of affordable housing, the terminological determination and definition of the term affordable housing, but also the clarification of the specific international legal obligations of states regarding the realization of the right to affordable housing, and the providing a basis for innovative legal solutions and models for realizing affordable housing in the Republic of Croatia.